Access to Dental Care for Head Start Enrollees - Burton L. Edefstein, DDS, MPH (Blackwell Synergy, 2000)
The objectives of this review are to characterize the oral health and dental access of Head Start children, describe barriers to their care, advance strategies to address those barriers, and consider how Head Start Performance Standards can be utilized fo maximize oral health and access to dental care.